Soft-template construction of three-dimensionally ordered inverse opal structure from Li2FeSiO4/C composite nanofibers for high-rate lithium-ion batteries. Issue 24 (2nd June 2016) - Li, Donglin; Zhang, Wei; Sun, Ru; Yong, Hong-Tuan-Hua; Chen, Guangqi; Fan, Xiaoyong; Gou, Lei; Mao, Yiyang; Zhao, Kun; Tian, Miao
Abstract : A 3DOM Li2 FeSiO4 /C architecture is constructed from small-sized nanofibers via a soft-template approach, which renders electrodes superior rate-performance. Abstract : Exploring a new method to fabricate small-sized nanofibers is essential to achieve superior performances for energy conversion and storage devices. Here, a novel soft-template strategy is developed to synthesize a three-dimensionally ordered macroporous (3DOM) architecture constructed from small-sized nanofibers. The effectiveness of a nanofiber-assembled three-dimensional inverse opal material as an electrode for high-rate lithium-ion batteries is demonstrated. The small-sized Li2 FeSiO4 /C composite nanofibers with a diameter of 20–30 nm are grown by employing a tri-block copolymer P123 as a structure directing agent. Accordingly, the macro–mesoporous hierarchical 3DOM architecture constructed from Li2 FeSiO4 /C nanofibers is further templated from P123 for the nanofibers and a polystyrene colloidal crystal array for the 3DOM architecture. We find that the thermal stability of the nanofiber morphology depends on the self-limited growth of Li2 FeSiO4 nanocrystals in a crystalline–amorphous hybrid. As a cathode for a lithium-ion battery, the 3D hierarchical macro–mesoporous cathodes exhibit outstanding high-rate and ultralong-life performances with a capacity retention of 84% after 1500 cycles at 5 C in the voltage window of 1.5–4.5 V, which is greatly improved compared with a simple 3DOM Li2 FeSiO4 /C nanocomposite.